Nematode Management on Athletic Fields - William T. Crow (EDIS)
Turfgrasses are essential components of many athletic fields, racetracks, and parks. Plant-parasitic nematodes can damage athletic fields by weakening turf root systems and causing turf to pull up during play, which can create dangerous conditions for players. To help keep turf and athletes healthy, this revised 7-page fact sheet explains how to spot and manage a nematode problem in an athletic field. Written by William T. Crow and published by the Department of Entomology and Nematology, February 2017.